Investigation on Electrically Conductive Aggregates as Grounding Compound Produced by Marconite - Mohd Yuhyi, Mohd Tadza; Tengku Hafidatul Husna, Tengku Anuar; Fadzil, Mat Yahaya (Universiti Malaysia Pahang, 2019)
Marconite is often used as alternative material to improve the performance of earth grounding system. This study aims to investigate of the physical and mechanical behaviour of conductive aggregate derived from Marconite namely, the electrical resistivity, water absorption, and crushing strength. In addition, similar tests were also conducted on mortar aggregate for comparison. The resistivity of aggregates were measured using soil box method. Test results showed that the electrical resistivity, water absorption, and crushing strength of both aggregates varied with time. These values were found to be stabilised after approximately after 14 days. The electrical resistivity for aggregates containing Marconite were found to be 39.2 Ω.m, far lower than 12700 Ω.m obtained for mortar-based aggregates. Similarly, the water absorption for Marconite aggregates were greater compared to mortar aggregates. On the other hand, the crushing strength for Marconite aggregates was to be lower. Incorporating Marconite significantly improved the electrical resistivity behaviour while maintaining acceptable mechanical properties crucial for electrical grounding purposes.